Drosophila MARF1 ensures proper oocyte maturation by regulating nanos expression. - Kawaguchi, S.; Ueki, M.; Kai, T. (PLoS ONE, 2020)
Meiosis and oocyte maturation are tightly regulated processes. The meiosis arrest female 1 (MARF1) gene is essential for meiotic progression in animals; however, its detailed function remains unclear. In this study, we examined the molecular mechanism of dMarf1, a Drosophila homolog of MARF1 encoding an OST and RNA Recognition Motif (RRM) -containing protein for meiotic progression and oocyte maturation. Although oogenesis progressed in females carrying a dMarf1 loss-of-function allele, the dMarf1 mutant oocytes were found to contain arrested meiotic spindles or disrupted microtubule structures, indicating that the transition from meiosis I to II was compromised in these oocytes. The expression of the full-length dMarf1 transgene, but none of the variants lacking the OST and RRM motifs or the 47 conserved C-terminal residues among insect groups, rescued the meiotic defect in dMarf1 mutant oocytes. Our results indicate that these conserved residues are important for dMarf1 function. Immunoprecipitation of Myc-dMarf1 revealed that several mRNAs are bound to dMarf1. Of those, the protein expression of nanos (nos), but not its mRNA, was affected in the absence of dMarf1. In the control, the expression of Nos protein became downregulated during the late stages of oogenesis, while it remained high in dMarf1 mutant oocytes. We propose that dMarf1 translationally represses nos by binding to its mRNA. Furthermore, the downregulation of Nos induces cycB expression, which in turn activates the CycB/Cdk1 complex at the onset of oocyte maturation.